2008
DOI: 10.1038/nrd2463
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological biomarkers for drug development in schizophrenia

Abstract: Schizophrenia represents a pervasive deficit in brain function, leading to hallucinations and delusions, social withdrawal and a decline in cognitive performance. As the underlying genetic and neuronal abnormalities in schizophrenia are largely unknown, it is challenging to measure the severity of its symptoms objectively, or to design and evaluate psychotherapeutic interventions. Recent advances in neurophysiological techniques provide new opportunities to measure abnormal brain functions in patients with sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
243
1
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 298 publications
(259 citation statements)
references
References 245 publications
(208 reference statements)
7
243
1
8
Order By: Relevance
“…Although some conflicting outcomes among different methodologies lead to continuous debate, several factors, including TCF4 (the transcription factor 4), erythroblastic leukemia viral oncogene 4 (ErbB4), zinc finger protein 804A (ZNF804a), and DISC1, are likely to enhance susceptibility to schizophrenia (2)(3)(4)(5)(6). Studies that explore molecular and functional interactomes have suggested that a cluster of such factors (e.g., molecular pathways) contributes significantly to functions of the glutamatergic synapse, in accordance with the classic concept that schizophrenia is a disorder of connectivity (7)(8)(9).…”
mentioning
confidence: 82%
“…Although some conflicting outcomes among different methodologies lead to continuous debate, several factors, including TCF4 (the transcription factor 4), erythroblastic leukemia viral oncogene 4 (ErbB4), zinc finger protein 804A (ZNF804a), and DISC1, are likely to enhance susceptibility to schizophrenia (2)(3)(4)(5)(6). Studies that explore molecular and functional interactomes have suggested that a cluster of such factors (e.g., molecular pathways) contributes significantly to functions of the glutamatergic synapse, in accordance with the classic concept that schizophrenia is a disorder of connectivity (7)(8)(9).…”
mentioning
confidence: 82%
“…The neurophysiological changes caused by acute administration of ketamine and believed to be associated with the psychotomimetic effects are broadly described (Hong et al, 2010;Javitt et al, 2008Javitt et al, , 2012Kocsis, 2012a;Kocsis et al, 2013). In contrast, neurophysiological mechanisms that may underlie the antidepressive effects of ketamine are much less explored.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, pre-pulse inhibition (PPI) of the acoustic startle response, a measure of sensorimotor gating, is diminished among individuals with schizophrenia as well as in healthy women during late pregnancy and the luteal phase of the menstrual cycle (Braff et al, 2001). PPI response has historically been considered a potential endophenotype for schizophrenia, and a number of drug development studies have focused on the capacity of a given drug to modulate the PPI as a model for potential efficacy in the treatment of schizophrenia (Braff and Light, 2005;Javitt et al, 2008). Hence, investigations of PPI in the pathophysiology and treatment of schizophrenia should take into consideration the reproductive status of the individual as gonadal steroids can modify PPI in both men and women.…”
Section: Sex As a Biological Variable Tl Bale And Cn Eppersonmentioning
confidence: 99%